2008
DOI: 10.1063/1.2832349
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing local moment versus itinerant ferromagnets: Dynamic magnetic susceptibility

Abstract: Radio-frequency measurements of dynamic magnetic susceptibility of various ferromagnets show striking differences between local-moment ferromagnetism (LFM) and weak itinerant ferromagnetism (IFM) ferromagnetic systems. LFMs show a very sharp peak in susceptibility in the vicinity of the Curie temperatureTC that rapidly decreases in amplitude and shifts to higher temperature with the application of a weak dc bias field. In stark contrast, the generally accepted IFM systems show no peak, but rather a broad maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…4 A possible solution is to use a purely itinerant electron ferromagnet compound in which all constituents are nonmagnetic, and then titrate in local moment-bearing ions. Currently, only two compounds, ZrZn 2 (Ref.…”
Section: Introductionmentioning
confidence: 99%
“…4 A possible solution is to use a purely itinerant electron ferromagnet compound in which all constituents are nonmagnetic, and then titrate in local moment-bearing ions. Currently, only two compounds, ZrZn 2 (Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In some concentrations the application of magnetic field also uncovers other features. This is most evident in the 50% cobalt doped sample where in fields of 0.6-1.1 kOe a well-defined peak in χ is observed in the vicinity of 20 K. Previous TDR rf susceptibility studies on other magnetic materials have shown that the presence of a well defined peak is indicitative of the onset of local moment ferromagnetic order [Vannette et al (2008d), Vannette et al (2008a), Vannette and Prozorov (2008)]. As the introduction of cobalt ions into the parent GdFe 2 Zn 20 lattice has been shown to suppress the itinerant component of the magnetism, the observation of features strongly associated with local moment magnetic order is not surprising.…”
Section: Parent Compoundsmentioning
confidence: 73%
“…The tunnel diode resonator technique is widely used for precision radio frequency (rf) magnetic susceptibility measurements of magnetic and superconducting materials with 1 : 10 7 frequency resolution measuring better than 0.1 Hz frequency shift at 10 MHz [34,35,30,31]. While in metallic samples the signal is a combination of skin effect and spin susceptibility, in insulating materials, such as the present case of spinice, it gives directly the real part of rf AC susceptibility up to a constant geometric factor.…”
Section: Methodsmentioning
confidence: 99%